Allocation of harvest between user groups in a fishery with habitat effect. (5th July 2018) - Nichols, Rachel; Yamazaki, Satoshi; Jennings, Sarah
Abstract : Abstract: The destructive impacts of fishing on marine habitats may be mitigated through the allocation of catch shares between different user groups. We assess the optimal allocation of harvest across multiple user groups and how fishery outcomes are affected when catch shares are allocated suboptimally. We incorporate the harvest allocation process into a bioeconomic model in which fishing‐induced habitat damage occurs and a single fish stock is targeted by two user groups characterized by fishing technologies of differing environmental impact. Results show that maximizing the overall profit of the fishery often requires the catch share of one of the groups to be set at zero. The effects on biological and economic outcomes of deviating from this allocation to ensure positive catch shares for all groups depend on the strength of habitat–fishery interactions, difference in fishing costs, and whether the suboptimal allocation is made to the high or low impact group. Recommedations for Resource Managers: Ignoring the impacts of fishing on marine environments can undermine attempts to sustainably manage fish stocks and to generate economic benefits that fisheries are capable of. Allocation of harvest across different fishery user groups is one means of managing habitat impacts of fishing. Economically optimal harvest allocation often requires the exclusion of either high impact user groups in a fishery where stocks are reliant on vulnerable habitats or low impact but less efficient user groups where habitat is fast to recover from damage. Suboptimal allocations of harvest need careful consideration as they may require trading‐off improved biological outcomes against lower fishery‐wide profit. Suboptimal allocations made in favor of a group causing higher habitat damage may result in collapse of fish stocks in environments where stocks are reliant on vulnerable environments and the damage rate of fishing is high.